Quality standards for the probative value of the Expert Accounting Report, under a technique and method approach (LACCEI, 2024)
The general objective of the investigation was to determine the importance of quality standards for the probative value of the Expert Report, type of basic investigation, descriptive level, quantitative approach, information collection technique was the survey and as an instrument the questionnaire, elaborated under the Likert scale, the validation was based on expert judgment, the population made up of 77 professional accountants, duly registered in the corresponding Registry of the College of Public Accountants of Cajamarca, Peru, the sample made up of 38 professional accountants, was used Inductive method, the main results were that the quality standards with respect to perception are very important for the probative value of the expert report, with a coefficient of 4.38 and a rating of very important In the same way, the Induction with a coefficient of 4.48 and a qualification of very important and finally the technique or opinion also considered as very important with a coefficient of 4.56, likewise the accounting experts use techniques of analysis, argumentation, calculations, technical method, documentary review, explanation and justification, apply methods such as the scientific one and perform calculations of the margin of error, among the main conclusions were that the quality standards for the probative value of the expert Report are very important and must be subject to joint consideration in such a way that it allows expert professionals to develop their service in a transparent and reliable manner, thus ensuring the probative effectiveness of expert reports